Sosialisasi pengolahan diverifikasi garam pangan (yodium dan fortifikasi ikan pepetek) untuk meningkatkan nilai jual garam di Desa Pesanggrahan-Madura - Salsabila, Marwa; Sultoni, Zahri Adelina; Samad, Novi Wandari; Kartika, Yemima Anindya; Ilhami, Salju Qolbi; Santoso, Moch. Bachtiar Eka; Riqin, Mohammad Haris; Septiana, Dita; Putra, Martha Anugrah Panca; Cahyono, Andree; Pangestuti, Sukma Ayundya; Ali, Abdul Warits Riyadi; Maulana, Aqil; Arifin, Samsul; Pratama, Ferdian Rizki; Asih, Eka Nurrahema Ning (Penamas: Journal of Community Service, 2024)
Intensive salt production using tunnels by salt farmers in Pesanggrahan Village is not optimal and is inversely related to the low selling price of salt in the village. The purpose of this socialization effort is to introduce the use of filters in salt ponds to improve the quality of kerosok salt production in tunnels and to provide guidance on verifying the types of iodine-enriched salt and fortified salt produced from tunnel salt. This activity involved five partners: three salt farmer groups (Makmur, Al-Islah, and Melati), the PKK women's group, and the Pesanggrahan Village Youth Organization. The community service activities included socialization and counseling on producing iodized and fortified salt in Pesanggrahan Village. The Likert scale survey results conducted after the socialization showed that 87% of participants understood the importance of using filters in the tunnels, while 13% did not. Additionally, 90% of participants understood how to make food-grade salt, while 10% still lacked this understanding.